Resilience for Sustainability: The Synergistic Role of Green Human Resources Management, Circular Economy, and Green Organizational Culture in the Hotel Industry - Ibrahim A. Elshaer; Alaa M. S. Azazz; Chokri Kooli; Khaled M. A. Alqasa; Jehad Afaneh; Eslam Ahmed Fathy; Amr Mohamed Fouad; Sameh Fayyad (Administrative Sciences)
This research explores the extent to which Green Human Resource Management (GHRM) practices in the Egyptian hotel sector contribute to the adoption of Circular Economy (CE) practices and, eventually, organizational resilience. Using a sample of 402 employees from green-certified Egyptian hotels, the current study applied Partial Least Squares Structural Equation Modeling (PLS-SEM) on the data collected. The results show the positive effect of GHRM on the adoption of a circular economy that significantly enhances both internal and external organizational resilience. In addition, high Green Organizational Culture (GOC) strengthens the positive relationship of GHRM with the adoption of a circular economy. From this work, some empirical evidence is provided to show that circular economy practices can play a partial mediating role between GHRM and organizational resilience. These findings also present valuable insights for hotel managers and policymakers on how to achieve sustainability and resilience by means of integrated GHRM and circular economy strategies.